تحسين كفاءة المرجل في معمل سمنة الخير باستخدام منهجية CUSUM - خضور, علي; الضابط, مدين; معروف, منار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Continuous improvement in energy management for industrial organizations is essential , because of issues range from the additional cost of energy processes due to inefficient utilization, vulnerability to price shocks of imported fuels etc., Monitoring and Targeting is a proven method for measuring and maintaining energy performance, and for identifying opportunities to improve energy efficiency. Key elements of an M&T Technique include: Measurement of utility (steam, fuel, power) consumption levels, The establishment of consumption targets that take variations in key variables into account, Comparison of actual vs. target energy usage, reports to highlight areas experiencing performance, An established protocol, involving both management and operating personnel, for reviewing and acting upon the energy information available. Tracking and reporting of the savings achieved. Through this study will determine the possibility of improving the efficiency of energy performance by cusum statistical technique after applying maintenance on the boiler. إن التحسين المستمر في إدارة الطاقة للمنظمات الصناعية أمر ضروري، وذلك بسبب التكلفة الإضافية لعمليات الطاقة والتي تعود الى عدم الكفاءة في الاستخدام، والتعرض لصدمات أسعار الوقود المستورد وما إلى ذلك. ويعتبر الرصد والاستهداف طريقة مؤكدة لقياس أداء الطاقة والحفاظ عليه، ولتحديد الفرص لتحسين كفاءة استخدام الطاقة. وتشمل العناصر الرئيسية لتقنية M & T ما يلي: قياس مستويات استهلاك المرافق (البخار والوقود والطاقة)، ​​ووضع أهداف الاستهلاك التي تأخذ في الاعتبار التغيرات في المتغيرات الرئيسية، مقارنة الاستخدام الفعلي مقابل الطاقة المستهدفة، التقارير لتسليط الضوء على المناطق التي تشهد أداء ضعيفا. بروتوكول معترف به يضم موظفي الإدارة والتشغيل على حد سواء لاستعراض المعلومات المتعلقة بالطاقة والعمل بها. تتبع وتقديم التقارير عن الوفورات المحققة. ومن خلال هذه الدراسة سيتم تحديد امكانية تحسين كفاءة أداء الطاقة بواسطة تقنية cusum الاحصائية بعد تطبيق الصيانة على المرجل.